Are gall midge species (Diptera, Cecidomyiidae) host-plant specialists? - Carneiro, MAA; Branco, CSA; Braga, CED; Almada, ED; Costa, MBM; Maia, V C; Fernandes, G W (Revista brasileira de entomologia, 2009)
Are gall midge species (Diptera, Cecidomyiidae) host plant specialists? Despite the speciose fauna of gall-inducing insects in the Neotropical region, little is known about their taxonomy. On the other hand, gall morphotypes associated with host species have been extensively used as a surrogate of the inducer species worldwide. This study reviewed the described gall midges and their galls to test the generalization on the use of gall morphotypes as surrogates of gall midge species in the Brazilian fauna. We compiled taxonomic and biological data for 196 gall midge species recorded on 128 host plant species. Ninety two percent of those species were monophagous, inducing galls on a single host plant species, whereas only 5.6% species were oligophagous, inducing galls on more than one congeneric host plant species. Only four species induced galls on more than one host plant genus. We conclude that gall morphotypes associated with information on the host plant species and attacked organs are reliable surrogates of the gall-inducing species.